2012
DOI: 10.7196/sajch.450
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and anthropometric profile of undernourished children aged under 5 admitted to Nyangabgwe Referral Hospital in Botswana

Abstract: Background. Although Botswana is a middle-income country, undernutrition among children younger than 5 years of age is still seen in various parts of the country. There is little information on the clinical and anthropometric profile of undernourished children in this age group admitted to hospitals in Francistown, Botswana. Purpose. To determine the clinical profile and the severity of anthropometric failure of undernourished children aged under 5 admitted to Nyangabgwe Referral Hospital in Francistown. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This indicates that it is not only lack or shortage of food that predisposes young children to malnutrition but also lack of knowledge on appropriate infant and young child feeding and care practices. 5 A Madondo, U E MacIntyre, B Ntuli study results show that 57.5% of the under-five malnourished children caregivers survived on less than 500 pula a month (equivalent to US$65.00), indicating poor income in a family affects child's development. Under-five Malnutrition children Admitted at the University of In Nigeria Teaching Hospital, Enugu: a 10 year retrospective review by Ngozi S Ibeziako et al study review noted that malnutrition was more common among children from the lower social class (69.4%) and those predominantly breast fed for three months or less (48.6%) compared to exclusively breast fed children (18.9%).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This indicates that it is not only lack or shortage of food that predisposes young children to malnutrition but also lack of knowledge on appropriate infant and young child feeding and care practices. 5 A Madondo, U E MacIntyre, B Ntuli study results show that 57.5% of the under-five malnourished children caregivers survived on less than 500 pula a month (equivalent to US$65.00), indicating poor income in a family affects child's development. Under-five Malnutrition children Admitted at the University of In Nigeria Teaching Hospital, Enugu: a 10 year retrospective review by Ngozi S Ibeziako et al study review noted that malnutrition was more common among children from the lower social class (69.4%) and those predominantly breast fed for three months or less (48.6%) compared to exclusively breast fed children (18.9%).…”
Section: Discussionmentioning
confidence: 93%
“…21 Dhrubajyoti J Debnath and Chandrakant V Parulekar study shows that children with illiterate mothers,from low standard of living are more prone to become malnourished. 5 A Madondo, U E MacIntyre, B Ntuli study results show majority of malnourished children's mothers (60%) were educated up to secondary school. A case-control study done by 4,10,14,8,12,15 Eskezyiaw Agedew showed that well educated mother's children were at statistically lower risk of being malnourished as compared to children of mother without education.…”
Section: Discussionmentioning
confidence: 94%